Integration of the production planning and execution process in enterprise management IT systems - Zasada, Jacek (Integracja procesu planowania i realizacji produkcji w informatycznych systemach zarządzania przedsiębiorstwem, 2021)
Nowadays, managers of manufacturing companies are facing more and more difficult decision-making problems to resolve. Fluctuations in demand and constantly growing markets place many requirements for planners to create a correct production schedule. Thanks to technological development it is possible to use systems supporting decision-making. However, not all systems work properly together. An example of problems with system integration is the implementation of a production monitoring system (MES) into an existing Enterprise Resource Planning(ERP) class system. This article aimed to show the use of the basic functions contained in the ERP system as part of the functions of the MES system. By integrating the ERP system with a mobile application, it becomes possible to obtain the basic functionalities of the MES system, i.e. monitoring of current production and confirmation of yield at the workplace. The article contains a short theoretical introduction regarding production schedule planning and the functions of ERP and MES class systems. The empirical part shows the diagnosed problems of the production company and an example of implementing an original solution, and is summed up with conclusions and guidelines for further stages of research.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 2 (60), s. 69-83
Keywords: ERP system; MES; supply chain management; production planning; logistics; system klasy ERP; zarządzanie łańcuchem dostaw; planowanie produkcji; logistyka